METHODOLOGY IN THE SYSTEM OF SCIENTIFIC AND NON-SCIENTIFIC KNOWLEDGE - Чорноморденко, І. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article studies the problem of methodology of science. Methodology of scientific knowledge and methodology beyond scientific knowledge are compared.